La leçon de choses selon Marie Pape-Carpantier - Bruno Klein (Recherches en Éducation)
The object lesson, a renowned didactic process, does not have the same definition for everyone. For Marie Pape-Carpantier (1815-1878), salle d'asile teacher, it represents the figurehead of the natural method and is enacted being instructive and moralising. We therefore propose to understand the spirit of these object lessons reserved for young children of the school which will later become pre-school. This pedagogic mechanism will be studied based on the body of works published over thirty years by the pedagogue specialised in young children. First contextualised, the objective will be to understand the mysteries of this lesson without forgetting its paradoxes.